The Development of An English Textbook Based on Local Wisdom to Improve the Students’ Literacy - Uspayanti, Rezky; Marnina, Marnina (Jurnal Paedagogy, 2024)
This research aims to develop an English textbook based on local wisdom to improve the students’ literacy. This research used a research and development (R&D) method with an ADDIE model, which consists of five stages, namely, analysis, design, development, implementation, and evaluation. The research subjects were the MA Almunawwaroh Merauke students for XI class. The research used tests, interviews, and questionnaires to collect the data. The data analysis technique was descriptive statistical analysis. The results of the research showed that the development of English books was in the good or feasible category. As the result of validation, based on assessment from the English lecturer, the content aspect before revision was 31 while after revision was 47, the presentation aspect before revision was 43, and after revision was 67, based language aspect where the stage before revision was 18 and after revision was 31, on the graphical aspect where the stage before revision was 28 and the stage after revision was 38. Based on the assessment of the English teacher, for the content aspect before revision, the score was 29 while the stage after the revision was 45, the presentation aspect where before the revision is 44, and after the revision was 66, on the language aspect where the stage before the revision was 19 and after the revision was 29, on the graphic aspect where the stage before the revision was 25 and the stage after the revision was 33. Furthermore, in the assessment of the principal based on content before revision the results of score is 28 while the stage after revision was 42, in the aspect of presentation before revision the overall score was 36, and after revision gets a score of 65, in the aspect of language where the stage before revision was 18 and after revision 29, in the aspect of graphics where the stage before revision was worth 23 and the stage after revision was worth 32. Before the book was used by all the students. The researchers did a trial by giving tests to students. Furthermore, the trial was conducted on 20 students. The students were given tests to know the students’ literacy after implementing the book. Furthermore, the trial was conducted on 20 students at MA Al-Munawwaroh by giving questions in the book that had been prepared, while the average value of the test results was 76.95.